Early Asian History - EAA Editorial Office (Education About Asia, 2021)
Given the publication this week of our “Teaching Asia in Middle Schools” issue, this month’s Digest Exclusive theme is Early Asian History. Each selection contains interesting “stories” for middle school teachers or non-specialists at any level who teach about early Asia in survey courses.
Keywords: Asia General; China; Education; India; Japan; Northeast Asia; Pedagogy; South Korea; World History